Are Student-Athletes Exploited? - James J. Heckman; Colleen P. Loughlin (Institute of Labor Economics (IZA), 2021)
The Supreme Court decision NCAA vs Alston (June 2021) heightened interest in the benefits and costs of participating in sports for student-athletes. Anecdotal evidence about the exploitation of student-athletes was cited in the opinion and the media. Using panel data, we follow two different cohorts of students from high school through college and beyond. We examine the accuracy of the anecdotes as descriptions of the actual experiences of student-athletes. We show that, on average, student-athletes either out-perform or perform the same as observationally identical non-athletes in terms of graduation and post-collegiate salaries. Participation in athletics promotes social mobility.
Keywords: Z2; Z22; I31; 330; social mobility; sports economics; exploitation